The Putative De-N-acetylase DnpA Contributes to Intracellular and Biofilm-Associated Persistence of Pseudomonas aeruginosa Exposed to Fluoroquinolones - Khandekar, Shaunak; Liebens, Veerle; Fauvart, Maarten; Tulkens, Paul M.; Michiels, Jan; Van Bambeke, Françoise (Frontiers in Microbiology, 2018)
Persisters are the fraction of antibiotic-exposed bacteria transiently refractory to killing and are recognized as a cause of antibiotic treatment failure. The putative de-N-acetylase DnpA increases persister levels in Pseudomonas aeruginosa upon exposure to fluoroquinolones in broth. In this study the wild-type PAO1 and its dnpA insertion mutant (dnpA::Tn) were used in parallel and compared for their capacity to generate persisters in broth (surviving fraction after exposure to high antibiotic concentrations) and their susceptibility to antibiotics in models of intracellular infection of THP-1 monocytes and of biofilms grown in microtiter plates. Multiplication in monocytes was evaluated by fluorescence dilution of GFP (expressed under the control of an inducible promoter) using flow cytometry. Gene expression was measured by quantitative RT-PCR. When exposed to fluoroquinolones (ciprofloxacin or levofloxacin) but not to meropenem or amikacin, the dnpA::Tn mutant showed a 3- to 10-fold lower persister fraction in broth. In infected monocytes, fluoroquinolones (but not the other antibiotics) were more effective (difference in Emax : 1.5 log cfu) against the dnpA::Tn mutant than against the wild-type PAO1. Dividing intracellular bacteria were more frequently seen (1.5 to 1.9-fold) with the fluoroquinolone-exposed dnpA::Tn mutant than with its parental strain. Fluoroquinolones (but not the other antibiotics) were also 3-fold more potent to prevent biofilm formation by the dnpA::Tn mutant than by PAO1 as well as to act upon biofilms (1-3 days of maturity) formed by the mutant than by the parental strain. Fluoroquinolones induced the expression of gyrA (4.5-7 fold) and mexX (3.6-5.4 fold) in the parental strain but to a lower extent (3-4-fold for gyrA and 1.8 to 2.8-fold for mexX, respectively) in the dnpA::Tn mutant. Thus, our data show that a dnpA insertion mutant of P. aeruginosa is more receptive to fluoroquinolone antibacterial effects than its parental strain in infected monocytes or in biofilms. The mechanism of this higher responsiveness could involve a reduced overexpression of the fluoroquinolone target.